Political Connections of Boards and the Selection of Auditors in Nigeria - Abdulmalik, O. Salau; Shittu, Isah; Ahmad, Ayoib Che (International Journal of Economics and Financial Issues, 2016)
The aim of this study is to examine the relationship between the political connections of board members and the selection of auditors by non-financial listed firms in Nigeria. The financial and non-financial information of 94 non-financial companies listed on the Nigerian Stock Exchange from 2008 to 2013 were analysed using a logistic regression model. The results of the logistic regression revealed that listed companies with politically connected board members were unlikely to appoint a Big 4 audit firm to audit their companies. This was likely because of difficulties in influencing such firms to issue an audit report in their favour. Regulatory bodies can use the outcome of this study to make necessary adjustments in codes directed at reducing the influence of political cronyism on the choice of auditor. Keywords: political connections, auditor selection, Nigeria JEL Classifications: M41, M42